Copper and zinc forms in soil fertilized with pig slurry in the bean crop - Grohskopf, Marco A. [UNESP]; Correa, Juliano C.; Cassol, Paulo C.; Nicoloso, Rodrigo S.; Fernandes, Dirceu M. [UNESP] (Univ Federal Campina Grande, 2016)
The application of pig slurry may have different influence on copper (Cu) and zinc (Zn) dynamics in the soil compared with mineral fertilization. The aim of this research was to determine the different forms of Cu and Zn in soil and their uptake by bean plants in response to the application of mineral fertilizer and pig slurry (PS). The treatments were: mineral fertilizer (Cu and Zn oxides) and liquid pig slurry, at increasing rates (0/0, 1.7/6.0, 3.4/12.0 and 6.8/24.0 kg ha(-1) Cu/Zn, respectively) applied in a Rhodic Kandiudox. PS increased the Cu content in soil in the exchangeable form, Fe oxides and residual, while the mineral fertilizer increased Cu contents in the fraction associated with soil organic matter. Soil Zn contents in the fractions available, exchangeable and SOM were highest under mineral fertilization, while in the soluble fraction the contents were highest under PS. The fertilizers had not impact on Cu and Zn contents associated with Al oxides, and these elements were mostly associated with Fe oxides in the soil. PS promoted the highest biomass production in shoots and roots of the bean plants, reflecting in the highest accumulation of Cu and Zn.
Keywords: swine slurry; uptake; metals fractionation